SISTEM KEMITRAAN DAN KELANGSUNGAN PEKERJAAN PETANI PERKEBUNAN KAKAO DESA BESOWO KEDIRI - Djohan, Eniarti B. (Fakultas Ilmu Sosial Universitas Negeri Padang, 2016)
This article is abstracted from the results of research on the partnership system and the continuity of the work of cocoa farmers in Besowo Kediri village. One of the strategies used to support the sustainability of the workforce in cocoa farming is to increase cooperation in partnership with various parties or institutions, both government, private, and inter-farmers in the development of cocoa plantation. The structure of the writing begins with the introduction as the background to the selection of issues discussed in this paper. Then this article continued a description of the factors that affect the cocoa farming partnership system in Besowo. This section describes the workings of Besowo villagers, factors affecting the cocoa farming partnership system, and the partnership form of the cocoa farmer community in Besowo Village. The next section is to review the continuity of the work of production activities and the employment opportunities of cocoa farmers. The last is the conclusion of this paper by connecting partnerships and continuity of work to improve the welfare of the family of plantation farmers.Keywords: Partnership system, cocoa farmer, cocoa plantation